Securitization of Cyber Threats: Implications for Privacy and Digital Rights - Garhwal, Sudhir Kumar and Pareek, Kumar Sambhav (Indian Journal of Political Science)
In today's fast-paced world of technological advancements and widespread digital connectivity, the securitization of cyber threats has become a pressing concern. As societies become increasingly reliant on digital infrastructure, the need for effective cyber- security measures is paramount. However, the securitization of cyber threats can have significant implications for privacy and digital rights. It examines the challenges and tensions that arise when balancing security imperatives with individual rights, while proposing potential solutions to mitigate the adverse consequences. This research paper explores the application of Securitization Framework to the field of cyber-security, aiming to enhance our understanding of cyber-security threats and their implications for privacy and digital rights. In this research paper, we focus on one case study that sheds light on the dynamics of securitization in the context of data breaches affecting personal privacy. By identifying securitizing actors, referent objects, analysing speech acts, and assessing audience acceptance, the paper uncovers similarities, differences, and contextual factors influencing securitization processes. The research identifies similarities and differences in securitization dynamics, explores the impact of cultural and contextual factors, and provides insights into the framing and perception of cyber threats. Additionally, the paper addresses challenges and critiques of applying the Securitization Framework to cyber-security and provides recommendations for refining its applicability. The research finding contribute to the understanding of cyber security securitization, informed policymaking in the realm of cyber-security, strategic decision-making, and the development of effective cyber-security measures.
Keywords: Securitization, cyber threats, privacy, digital rights, cyber-security, Technology